Light-driven eosin Y-Ralstonia eutropha biohybrid for CO2 conversion to acetoin via specific photo-induced electron transfer and metabolic engineering - Yao Tian; Zhiqi Guo; Jiaping He; Dake Xu; Wen-Wei Li; Shaoan Cheng; Hao Song (Journal of CO2 Utilization, 2025)
Whole-cell photosynthetic biohybrid systems offer a promising route for CO2 conversion into value-added chemicals. However, many existing systems suffer from inefficient electron transfer to intracellular catalytic CO2 center, which arises from non-specific charge transfer between photosensitizer and microbe. Herein, we developed an efficient eosin Y-Ralstonia eutropha biohybrid system that achieved targeted electron transfer for powering CO2 reduction into acetoin, a valuable platform chemical with broad applications. By spontaneously attaching eosin Y to the membrane-bound hydrogenase (MBH) of R. eutropha, we enabled direct and specific electron flow. The biohybrid system demonstrated sustainable and efficient light-energized CO2 conversion to acetoin, even surpassing the yields from H2-supplied autotrophic fermentation, which is considered the optimal source of reducing equivalents and energy for CO2 fixation by R. eutropha. Mechanistic investigations indicated that the photo-induced electrons from eosin Y were transferred to MBH, resulting in the formation of H2 intermediate in periplasm, which was subsequently oxidized by cytosolic soluble hydrogenase to generate NADH for energizing CO2 fixation. To further enhance efficiency, metabolic engineering was applied to boost ATP synthesis by introducing a non-oxygen-dependent proton pump (Gloeobacter rhodopsin), while blocking L-lactate and acetate biosynthesis pathways to divert carbon flux toward acetoin production. The engineered eosin Y-R. eutropha biohybrid system achieved an acetoin yield of 1.41 ± 0.06 mM, representing 2.07 times greater than that of H2-supplied autotrophic fermentation. This system exemplifies a sustainable, light-driven CO2 conversion process, contributing significantly to the advancement of sustainable biocatalytic processes in the realms of green chemistry and CO2 management.